Factors Affecting Saving, Policy tools, and Tax Reform : A Review. (IMF Working Papers; Working Paper ;, 1989)
This paper reviews the literature on factors which affect saving and capital formation in industrialized countries. Problems of measurement are briefly examined. Evidence of the effect on the rate of saving of real rates of return, income redistribution, allocation of saving between corporations and individuals, growth of public and private pension plans, tax incentives, and many other factors ranging from the bequest motive to energy prices and inflation, is considered. Given this evidence, the limited tools available to policymakers to affect savings are discussed. Finally, the extent to which recent tax reforms in a number of countries appear to have been affected by the desire to increase saving is reviewed.